HEALTH SEEKING BEHAVIOR DI KALANGAN MASYARAKAT URBAN DI KOTA YOGYAKARTA - Aris Widayati (Universitas Sanata Dharma, 2016)
Abstract : Research presented in this article investigated health seeking behavior among people in an urban area of Yogyakarta City Indonesia. The research was a cross-sectional survey involved adults in Yogyakarta City who were selected using a cluster random sampling technique. Sample size was 640 respondents. Data were collected using a pre-tested questionnaire during March to May 2010. Data were analyzed using descriptive statistics, Chisquare tests, and Logistic regression. A total of 559 questionnaires were completed, resulted in 90% of response rate. Mostly respondents stated that they had one to three medical complaints within a month (51% of 559). The most popular health seeking behavioris a combination between self-care and consultation to health care providers (41%). Other options are self-care (36%), consultation to public health care centre (16%), and consultation to private health care (5%). Among the socio-demographic and economic characteristics, marital status is the only factor that significantly correlated with health seeking behavior. Based on the results it can be recommended that programs for improving health behavior should consider self-care, including no medication and self medication with modern and herbal/traditional medicines. The role of family members (e.g. spouse) should also be considered as an important factor of health related behavior. Keywords : Health seeking behavior